THE INFLUENCE OF FRONT LINER SERVICEABILITY ON CUSTOMER SATISFACTION AT RIAU KEPRI BANK BENGKALIS BRANCH OFFICE - Nur Asikin; Hutomo Atman Maulana (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
This research was conducted to determine the influence of front liner services ability on customer satisfaction at Riau Kepri Bank, Bengkalis branch office. Front liner serviceability in this research was limited to the intellectual and physical ability of teller and customer service. The population in this research were all the people who have used products or services at Riau Kepri Bank Bengkalis branch office. There were 100 respondents as samples were taken by using the purposive sampling technique. Data was collected by using online questioners that consist of 22 questions with Likert scale. This research used multiple linear regression as a data analysis technique. The results showed that intellectual ability has a positive and significant effect on customer satisfaction partially (t=2.932, p=0.004), the physical ability also has a positive and significant effect on customer satisfaction partially (t=3.072, p=0.003), and simultaneously, the intellectual and physical ability of front liner has a positive and significant effect on customer satisfaction at Riau Kepri Bank Bengkalis branch office (F=23.717, p=0.000, R2=0.32).